Future Feasibility of Using Wearable Interfaces to Provide Social Support - Wilde, Natalie; Haddadi, Hamed; Alomainy, Akram (EAI Endorsed Transactions on Smart Cities, 2015)
Social support has a positive influence on a person's overall wellbeing. Recent creation of mobile and online social networks have changed the methods used to obtain such support. Previous wearable devices have focussed on increasing an individuals perceived social support by either encouraging new social relationships or strengthening those already existing. With the release of the Apple Watch, wearable interfaces are becoming popular but there is little research into the current attitudes of using these interfaces as a social support medium. In this paper we present results of our survey to establish the attitudes of current smartwatch owners. Results show owning a smartwatch has no effect on the levels of social support a person feels they have. The most commonly used method of support was through smartphone, which was true for people regardless of whether they own a smartwatch. A large number of smartwatch owners stated using their device was their last preference in seeking emotional (61%) and informational (57%) support from others. Results from the survey indicate that more research is needed to establish exactly what factors make technological devices well suited to accommodate social support and how these can be applied to wearable interfaces in the future.
Keywords: smart watch; wearable interfaces; social networks